Peran Komunitas Kawan Pasar Kamu dalam Pelestarian Kearifan Lokal Musik Melayu Pakpung di Desa Denai Lama - Arum Dwi Saputri; Rosdiana (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This study aims to analyze the role of the Kawan Pasar Kamu Community in preserving the local wisdom of Pakpung Malay Music in Denai Lama Village through facilitative, educational, representative, and technical roles. This study uses a descriptive qualitative approach with purposively selected informants, namely the community leader and two members who act as artists, Pakpung drum-making instructors, and Pakpung Malay Music players. Data were collected through observation, interviews, and documentation, then analyzed using the Miles and Huberman model. The results show that these four roles form a complementary preservation ecosystem. The facilitative role provides space, opportunities, and means to maintain the sustainability of musical practices; the educational role transmits knowledge, skills in playing music and making Pakpung drums, as well as Malay cultural values; the representative role expands the existence of Pakpung Malay Music through performances and social media; while the technical role ensures the sustainability of activity management and maintenance of musical instruments. Thus, the Kawan Pasar Kamu Community contributes not only to maintaining the practice of Pakpung Malay Music, but also to passing on knowledge, skills, and cultural values ​​to the younger generation and expanding public recognition of the existence of this music as part of local wisdom.